Prevalence of Anesthesia Complications in Orthopedic Surgeries and its Related Factors - Hossein Kiani; Masoumeh Hoseinian; Zohreh Sadat; Neda Mirbagher Ajorpaz (Iran University of Medical Sciences, 2021)
Background: The duration of surgery in orthopedic surgeries is often longer than one hour. Therefore, these patients are at further risk of complications induced by general anesthesia. The present study aimed to determine the prevalence of anesthesia complications in orthopedic surgeries and its related factors.  Methods: This cross-sectional study was performed on 400 patients undergoing orthopedic surgery in Shahid Beheshti Hospital of Kashan Province, Iran, in 2020. The study subjects were recruited by convenience sampling method. We included those who similarly underwent general anesthesia for elective surgery and were transferred to Post-Anesthesia Care Unit (PACU). The research instruments included a demographic questionnaire and a checklist for recording complications (shivering, pain, nausea, vomiting, & vital signs). The necessary data were recorded after the patient was admitted to the PACU, as well as half an hour and one hour later. The obtained data were analyzed using the Chi-squared test, Independent Samples t-test, one-way Analysis of Variance (ANOVA), Pearson correlation coefficient, and logistic regression analysis in SPSS v. 16. Results: The present research results suggested that the most and least frequent complications were vomiting (91.8%) and changes in blood pressure (5%), respectively. Gender was significantly associated with pain, nausea, and hypertension (P<0.05). The Pearson correlation coefficient data indicated a significant relationship between the duration of anesthesia and the mean scores of shivering, pain, nausea, tachycardia, and tachypnea (P<0.05). There was also a significant relationship between the types of surgery and shivering, pain, blood pressure, and nausea (P<0.05). Pulse rate was significantly associated with complete intravenous anesthesia and the duration of anesthesia (P<0.05). Conclusion: The relatively high incidence of post-anesthesia complications in orthopedic surgeries indicates the significance of employing skilled personnel as well as using adequate monitoring equipment at the PACU. Such measures help to decrease mortality and morbidity among patients, also save on hospital costs.